Rediscovery of Micryletta inornata (Boulenger, 1890) from Sumatra: redescription, molecular identity, and taxonomic implications - Alhadi, Farits; Hamidy, Amir; Farajallah, Achmad; Munir, Misbahul; Atmaja, Vestidhia Y.; Garg, Sonali; Biju, S. D.; Smith, Eric N. (Zootaxa, 2019)
Micryletta inornata (Boulenger 1890), the type species of the genus Micryletta, was originally described from the island of Sumatra in Indonesia. Subsequently, this species has been widely reported from Sundaland (Sumatra and Malay Peninsula), Indo-China, Northeast India and South Andaman, up to southern China and Taiwan. However, since the original description there has been no further report of this species from the type locality or the island. During a herpetofaunal survey in Sumatra, several specimens that are morphologically concordant with the original description and the syntypes of M. inornata were found, and thus the species was rediscovered after 125 years. Here, we provide a redescription of the species based on the freshly collected specimens, along with a detailed morphological and molecular comparison with known congeners. Further, using molecular data from the mitochondrial 16S rRNA gene, our study recovered the Sumatran M. inornata as a phylogenetically distinct lineage from all other populations previously referred to this species. This confirms that all known Micryletta ‘inornata’ populations from regions outside Sumatra constitute several other lineages representing either new species or previously available names currently considered as synonyms, consequently requiring taxonomic validation in the future.